2022
DOI: 10.1097/mao.0000000000003661
|View full text |Cite
|
Sign up to set email alerts
|

Is Idiopathic Sudden Sensorineural Hearing Loss Seasonal?

Abstract: ObjectiveTo investigate the circannual rhythm (seasonal incidence) of idiopathic sudden sensorineural hearing loss (ISSNHL).MethodsData were retrieved from the medical files of an original cohort of all consecutive patients with ISSNHL in a tertiary medical center between 2012 and 2020. A systematic literature search of “MEDLINE” via “PubMed,” “Embase,” and “Web of Science” on comparable published cases was performed. A Google Trends analysis of the term [sudden hearing loss] and related terms between 2014 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Additionally, a preliminary report has indicated a seasonal pattern of SSNHL episodes. The results showed that the incidence of SSNHL was lowest in winter and highest in spring (Simani et al 2022 ). However, no study has been conducted using advanced statistical models to systematically quantify and assess the influence of meteorological variables containing the temperature mean (T-mean), diurnal temperature range (DTR), atmospheric pressure (AP), relative humidity (RH), and wind speed on SSNHL, despite the previously clarified role of ambient temperature in SSNHL.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a preliminary report has indicated a seasonal pattern of SSNHL episodes. The results showed that the incidence of SSNHL was lowest in winter and highest in spring (Simani et al 2022 ). However, no study has been conducted using advanced statistical models to systematically quantify and assess the influence of meteorological variables containing the temperature mean (T-mean), diurnal temperature range (DTR), atmospheric pressure (AP), relative humidity (RH), and wind speed on SSNHL, despite the previously clarified role of ambient temperature in SSNHL.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the number of patients diagnosed with sensorineural hearing loss who continued to visit the clinic year after year increased signi cantly and steadily. A study examining the circadian rhythm (seasonal incidence) of sudden hearing loss found that it was seasonal and increased during the spring months of March, April, and May 21 . When analyzed by differencing, out of the eight types, only sudden hearing loss showed signi cant seasonality, with a consistent increase in the number of patients in winter.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, I think it is the result of a well-reflected study that sensory neurotic hearing loss accounts for the most types of Gap hearing loss. A study examining the circadian rhythm (seasonal incidence) of sudden hearing loss found that it was seasonal and increased during the spring months of March, April, and May [21]. When analyzed by differencing, out of the eight types, only sudden hearing loss showed significant seasonality, with a consistent increase in the number of patients in winter.…”
Section: Plos Onementioning
confidence: 99%